The shocking secret of a guest at the wedding ebook - Alexander, Victoria (Millworth Manor., 2014)
#1 New York Times –bestselling author: " Droll banter . . . Well-placed plot twists . . . Jack and Teddy are two of [Alexander's] all-time finest creations." — Publishers Weekly The bride and groom cordially request your presence for a wedding at Millworth Manor . . . Guests will include Jackson Quincy Graham Channing, New York City banker, and Lady Theodosia "Teddy" Winslow, wedding planner to the finest families in England. Introductions shall be followed by light conversation, dancing, flirtation, arguing, reconciliation, and an impulsive kiss that both parties are quite certain they will never repeat. Until they do. A mutually beneficial fake engagement will be accompanied by all manner of very real complications, scandalous revelations, nefarious schemes, and one inescapable conclusion: That true love—unlike the perfect wedding—is impossible to plan . . . "Readers will come for the romance and stay for the family dramas." — Kirkus Reviews Praise for the writing of Victoria Alexander "Sparkling dialogue and endearing characters make this an enthralling read." —Sabrina Jeffries "Wickedly funny historical romance." — Booklist